2016
DOI: 10.1093/ofid/ofw008
|View full text |Cite
|
Sign up to set email alerts
|

Miltefosine for Mucosal and Complicated Cutaneous Old World Leishmaniasis: A Case Series and Review of the Literature

Abstract: Complicated Old World cutaneous leishmaniasis (OWCL) and Old World mucosal leishmaniasis (OWML) constitute an indication for systemic treatment. To date, there no controlled clinical studies that compare treatment options for these diseases. We compiled a case series of 24 cases successfully treated with miltefosine. We conclude that oral miltefosine is an effective treatment option for both OWCL and OWML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 23 publications
0
30
0
3
Order By: Relevance
“…Local treatment proved to be well tolerated and with high cure rates and includes topical treatment with 15% paromomycin, cryotherapy, thermotherapy and intralesional injection with antimonials . Systemic treatment includes miltefosine, fluconazole, liposomal amphotericin B, systemic pentavalent antimonial or systemic pentavalent antimonial and pentoxifylline …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local treatment proved to be well tolerated and with high cure rates and includes topical treatment with 15% paromomycin, cryotherapy, thermotherapy and intralesional injection with antimonials . Systemic treatment includes miltefosine, fluconazole, liposomal amphotericin B, systemic pentavalent antimonial or systemic pentavalent antimonial and pentoxifylline …”
Section: Discussionmentioning
confidence: 99%
“…Mucosal leishmaniasis pathophysiology in the Mediterranean region remains unclear as it is usually not associated with previous CL; the spectrum of clinical manifestations may vary from single to multiple lesions that can manifest as a nodule, tumor, polypoid lesion or granular inflammation and predominantly involve the buccal area (cheeks, lips, hard and soft palate and gums) and the pharyngeal and laryngeal area . Less frequently, the nose can be affected …”
Section: Introductionmentioning
confidence: 99%
“…Although some authors have reported successful treatment of lesions with local therapies, 3 there may be lesions in other unrecognized sites, therefore systemic treatment with pentavalent antimonials, amphotericin B or miltefosine seems the most prudent option. 1,3,6 We treated our patient with intravenous liposomal amphotericin B, which resulted in complete remission of the lesions.…”
Section: P Dmentioning
confidence: 99%
“…The treatment of cutaneous and mucosal leishmaniasis in SOT is not standardized, but most of the cases have been successfully treated with lipid formulation of AMB or antimonials. The role of newer drugs like miltefosine needs to be defined but it has been successfully used in immunocompetent patients . The overall prognosis of these lesions is generally excellent.…”
Section: Solid Organ Transplant Recipientsmentioning
confidence: 99%
“…The role of newer drugs like miltefosine needs to be defined but it has been successfully used in immunocompetent patients. 45,67,68 The overall prognosis of these lesions is generally excellent.…”
Section: Cutaneous and Mucocutaneous Leishmaniasesmentioning
confidence: 99%